Digital Manufacturing Transformation in the Automotive Industry: A Technical Analysis - Kumar Rajiv Nayan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The automotive manufacturing sector is experiencing a profound transformation driven by Industry 4.0 principles and digital technologies. This comprehensive article examines the evolution of smart manufacturing technologies, their impact on production processes, and the resulting paradigm shift in automotive manufacturing operations. The article explores the implementation of digital twins, advanced manufacturing systems integration, cybersecurity frameworks, and workforce development strategies. The article highlights how these technological advancements have revolutionized production efficiency, quality control, and market responsiveness while addressing the challenges of legacy system integration and cybersecurity. Furthermore, it investigates the future trajectory of automotive manufacturing, focusing on additive manufacturing technologies, artificial intelligence applications, and software-defined vehicle production methodologies.
Keywords: Digital Manufacturing; Industry 4.0; Smart Manufacturing; Digital Twin Technology; Manufacturing Systems Integration